2013
DOI: 10.1002/em.21795
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate remediation of cell stress and genotoxicity induced by haloacetic acid drinking water disinfection by‐products

Abstract: Monohaloacetic acids (monoHAAs) are a major class of drinking water disinfection by-products (DBPs) and are cytotoxic, genotoxic, mutagenic, and teratogenic. We propose a model of toxic action based on monoHAA-mediated inhibition of glyceraldehyde-3-phosphate dehydrogenase (GAPDH) as a target cytosolic enzyme. This model predicts that GAPDH inhibition by the monoHAAs will lead to a severe reduction of cellular ATP levels and repress the generation of pyruvate. A loss of pyruvate will lead to mitochondrial stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 51 publications
2
59
0
Order By: Relevance
“…Besides, the toxicity rank orders of two additional groups of halo-DBPs (4-halophenols and 3,5-dihalo-4-hydroxybenzaldehydes) for the alga also followed this pattern, i.e., 4-iodophenol > 4-bromophenol > 4-chlorophenol; and 3,5-diiodo-4-hydroxybenzaldehyde > 3,5-dibromo-4-hydroxybenzaldehyde > 3,5-dichloro-4-hydroxybenzaldehyde. The same toxicity rank order of monohaloacetic acids has also been reported in the bioassays for different organisms Pals et al, 2013;Dad et al, 2013). Third, DBP isomers presented varying levels of toxicity.…”
Section: 2mentioning
confidence: 69%
See 2 more Smart Citations
“…Besides, the toxicity rank orders of two additional groups of halo-DBPs (4-halophenols and 3,5-dihalo-4-hydroxybenzaldehydes) for the alga also followed this pattern, i.e., 4-iodophenol > 4-bromophenol > 4-chlorophenol; and 3,5-diiodo-4-hydroxybenzaldehyde > 3,5-dibromo-4-hydroxybenzaldehyde > 3,5-dichloro-4-hydroxybenzaldehyde. The same toxicity rank order of monohaloacetic acids has also been reported in the bioassays for different organisms Pals et al, 2013;Dad et al, 2013). Third, DBP isomers presented varying levels of toxicity.…”
Section: 2mentioning
confidence: 69%
“…Numerous studies have been conducted on the comparative toxicity of haloaliphatic DBPs in drinking water using different bioassay species, including bacteria, Chinese hamster ovary cells, and human cells. These studies have shown that iodo-DBPs were generally significantly more cytotoxic and genotoxic than their bromo-analogues, which in turn were more toxic than their chloro-analogues (Plewa et al, , 2008a(Plewa et al, , 2008bEchigo et al, 2004;Richardson et al, 2007;Richardson et al, 2008;Dad et al, 2013;Pals et al, 2013). Most recently, Yang and Zhang (2013) conducted toxicity tests for 24 halo-DBPs (most of which were newly identified in chlorinated saline wastewater effluents) using a marine polychaete Platynereis dumerilii, and found that this toxicity rank order (i.e., iodo-DBPs > bromoanalogues > chloro-analogues) applied also to the heterotrophic marine polychaete; moreover, the newly identified halophenolic DBPs were significantly more toxic than commonly known trihalomethanes and haloacetic acids, most of which have been regulated in the Disinfectants/DBPs rule by the U.S. EPA (2006).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The primary cellular target molecule for the monohaloacetic acids (monoHAAs) is glyceraldehyde-3-phosphate dehydrogenase (GAPDH) (57). Inhibition of GAPDH leads to pyruvate starvation and mitochondrial stress that generates ROS (58,59). New research demonstrated that the monohalonitriles, at non-cytotoxic concentrations, impact the M-phase of the cell cycle and induce hyperploidy in mammalian cells (35).…”
Section: Molecular Mechanisms Of Action Of the Dbp Forcing Agents Assmentioning
confidence: 99%
“…Although the exact mechanism of IAA toxicity is unclear, 35) neural cells exposed to IAA present with an increased production of ROS, 36) leading to mitochondrial stress and DNA damage. 37,38) Since TMP can maintain mitochondrial function and suppresses ROS generation, 9) TMP was found to significantly prevent PC12 cells against IAA-induced neurotoxicity at 1-100 µM. However, TMP was less potent than 8a, b, 12a and 22a, b (Fig.…”
Section: )mentioning
confidence: 97%